2006
DOI: 10.1074/jbc.m513725200
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Stabilities of the Structural Repeats of Erythroid Spectrin and Their Functional Implications

Abstract: The two polypeptide chains of the erythroid spectrin heterodimer contain between them 36 structural repeating modules, which can function as independently folding units. We have expressed all 36 and determined their thermal stabilities. These vary widely, with unfolding transition mid-points (T m ) ranging from 21 to 72°C. Eight of the isolated repeats are largely unfolded at physiological temperature. Constructs comprising two or more adjacent repeats show inter-repeat coupling with coupling free energies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
76
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 33 publications
5
76
0
1
Order By: Relevance
“…Binding of RESA to ␤1R16 spectrin structural repeat close to the interaction region between ␣1 and ␤1 spectrins significantly increases the stability of spectrin tetramers (24). In healthy RBCs, the spectrin network exists in a dynamic state of spectrin tetramers dissociating transiently into dimers, and shear deformation shifts the equilibrium of tetramer formation toward the dissociated dimer state (25). Thus, RESA stabilization of tetramers could modify spectrin network dynamic properties, thereby impairing membrane deformability.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of RESA to ␤1R16 spectrin structural repeat close to the interaction region between ␣1 and ␤1 spectrins significantly increases the stability of spectrin tetramers (24). In healthy RBCs, the spectrin network exists in a dynamic state of spectrin tetramers dissociating transiently into dimers, and shear deformation shifts the equilibrium of tetramer formation toward the dissociated dimer state (25). Thus, RESA stabilization of tetramers could modify spectrin network dynamic properties, thereby impairing membrane deformability.…”
Section: Discussionmentioning
confidence: 99%
“…The design of all αII-and βII-spectrin single repeats and tandem-repeat fragments followed that for αI-and βI-spectrin fragments (20). The residue numbers of all sequences are given in Table 1.…”
Section: Design and Subcloning Of Recombinant Brain Spectrin Polypeptmentioning
confidence: 99%
“…Having previously found that the repeating units of αI-and βI-spectrin vary widely in their thermostabilities (20), we were prompted to examine those of αII-and βII-spectrins to investigate the basis of the differences in the gross characteristics of the intact proteins. We have accordingly determined the thermal unfolding properties of each repeat of αII-and βII-spectrin, as well as some constructs comprising selected tandem pairs of repeats, and some with mutations in the single α-helix uniting them.…”
mentioning
confidence: 99%
“…1A. All recombinant proteins were expressed at 16°C, at which the yield was optimal, and allowed the isolation of soluble products in a state of high purity (11,26). The structure of the PfEMP3 protein is illustrated in Fig.…”
Section: Mapping the Pfemp3 Binding Site In Spectrin-mentioning
confidence: 99%